Spatiotemporal distributions of brain oscillation during silent reading - Hirata, Masayuki; Kato, Amami; Ninomiya, Hirotomo; Taniguchi, Masaaki; Kishima, Haruhiko; Yoshimine, Toshiki (International Congress Series, 2002)
The purpose of this study is to demonstrate the spatiotemporal distributions of event-related desynchronization (ERD) and synchronization (ERS) during silent reading. One hundred of three-character hiragana semantic words were presented serially on a liquid crystal monitor for 3 s, and with intervals of 3 s. Six healthy right-handed subjects were instructed to read them without phonation. The data were measured using whole-head type magnetometer. The current sources were estimated spatiotemporally by synthetic aperture magnetometry (SAM). Changes in the source power between the active state and the control state were analyzed statistically with Student's t values. ERD and ERS were distributed multifocally over both hemispheres including classically language-related regions, and lateralized to the left hemisphere. ERSs tended to be distributed serially from the occipital region via the parieto-temporal region to the frontal region. ERDs tended to be distributed multifocally in parallel. Both serial and parallel processings are suggested to be involved in the silent reading. Spatiotemporal distributions and frequency bands of ERD definitely differed from those of ERS. ERS and ERD might reflect the excitation and inhibition of different Hebbian cell assemblies.